2013
DOI: 10.1038/ejcn.2013.252
|View full text |Cite
|
Sign up to set email alerts
|

Conclusiveness of the Cochrane Reviews in Nutrition: a systematic analysis

Abstract: The majority of CRs in Nutrition is conclusive, but most of them emphasize the need for further studies. The ability for a CR to reach a conclusion is affected by the cumulative patient sample size and number of RCT's included in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
(8 reference statements)
1
20
0
Order By: Relevance
“…These findings are inconsistent with the hypothesis that the majority of reviews are inconclusive. [3][4][5] Reviews of RCTs were more likely to be conclusive than those of nonrandomized studies (63.8% vs 50.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are inconsistent with the hypothesis that the majority of reviews are inconclusive. [3][4][5] Reviews of RCTs were more likely to be conclusive than those of nonrandomized studies (63.8% vs 50.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of RCTs, however, are likely to be conclusive and provide practical answers regarding what works (or what may work) in a particular clinical situation. 4 Although it is possible to make a decision based on conclusive reviews, the quality of included RCTs and the review itself should be assessed. 6,7 The methodological quality of review articles is assessed using the AMSTAR tool.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the goals of the Cochrane reviews are not always reached: indeed, not all Cochrane reviews are conclusive and even when they are it is often stated that there is a need for more and better studies [35]. Based on previous reports, 64–80% of Cochrane reviews are conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports, 64–80% of Cochrane reviews are conclusive. However, a majority emphasizes the need for further studies [35]. Therefore, approximately one out of three times the reader is not able to reach a clinically applicable conclusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation